2014
DOI: 10.1039/c4ob00096j
|View full text |Cite
|
Sign up to set email alerts
|

Amplification by nucleic acid-templated reactions

Abstract: Nucleic acid-templated reactions enable the design of conditional reaction systems, in which bond formation occurs only when a particular DNA or RNA molecule is present. Such reaction systems are currently being explored for applications in DNA/RNA diagnosis, drug screening and as a means to design gene expression specific therapy. However, biological nucleic acid templates usually have low abundance. Therefore, either the targeted nucleic acid template has to be multiplied by means of an amplification step or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
48
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 103 publications
0
48
0
Order By: Relevance
“…PCR is not an option for reactions that ought to proceed in biological samples. Ideally, the templated reaction should provide for turnover in the target strand . In this case, each target molecule would instruct the formation of many product molecules.…”
Section: Termolecular Assemblies For Nucleic Acid–programmed Peptide mentioning
confidence: 99%
See 1 more Smart Citation
“…PCR is not an option for reactions that ought to proceed in biological samples. Ideally, the templated reaction should provide for turnover in the target strand . In this case, each target molecule would instruct the formation of many product molecules.…”
Section: Termolecular Assemblies For Nucleic Acid–programmed Peptide mentioning
confidence: 99%
“…Ideally, the templated reaction should provide for turnover in the target strand. 97,98 In this case, each target molecule would instruct the formation of many product molecules. However, nucleic acid-templated ligation reactions suffer from product inhibition.…”
Section: Termolecular Assemblies For Nucleic Acid-programmed Peptidmentioning
confidence: 99%
“…Various chemical ligation reactions have been applied to non-enzymatic sequencing of ONs (5), ON-based diagnosis (6), biotechnology (2,7) and nanotechnology for making functional nanoconstructs (811). In general, the chemical ligation between two functional groups requires the presence of condensing reagents.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, a variety of functional group pairs, for example, a nucleophilic group and an electrophilic group, or alkyne and azide groups, have been examined for use in chemical ligations with various applications in biology and biotechnology (2,20). ON-templated reactions without using any extra reagents were developed (2,7,21,22), and they are related to the study on the origin of life (23). These types of reactions are especially suitable for chemical ligations in biological contexts such as in cells, for RNA detection (3) or intracellular build-up of siRNA species (4).…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] One major challenge facing nucleic-acid based point-of-care (POC) diagnostics is the low concentration of nucleic acid biomarkers in all biologically extracted samples. [6][7][8] As such, multiple examples of POC diagnostics using enzyme-based isothermal amplification methods have been reported that avoid the expensive instrumentation necessitated by the temperature cycling steps of the polymerase chain reaction. [6][7][8] As such, multiple examples of POC diagnostics using enzyme-based isothermal amplification methods have been reported that avoid the expensive instrumentation necessitated by the temperature cycling steps of the polymerase chain reaction.…”
mentioning
confidence: 99%